2005
DOI: 10.1124/jpet.105.088047
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CYP2E1-Dependent Oxidant Stress on Activity of Proteasomes in HepG2 Cells

Abstract: A reduction in proteasome activity and accumulation of oxidized proteins may play a role in alcoholic liver disease. The current study assessed proteasome peptidase activities and oxidative modifications of proteasomes during oxidative stress generated by CYP2E1. The model of toxicity by arachidonic acid (AA) and iron [ferric-nitrilotriacetate (Fe-NTA)] in HepG2 cells overexpressing CYP2E1 (E47 cells) and control C34 cells was used. AA/Fe-NTA treatment decreased trypsin-like (T-L) activity of the proteasome in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
(44 reference statements)
3
25
0
Order By: Relevance
“…Previous studies showed that inhibition of the proteasome activity is a major mechanism that causes increased accumulation of ubiquitinated proteins, which are normally degraded by the cellular proteasome machinery (Chung et al, 2005;Kessova and Cederbaum, 2005;Marteijn et al, 2005;Zhang et al, 2005). We therefore tested whether AM114 might inhibit proteasome activity, leading to the accumulation of ubiquitinated proteins in the cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that inhibition of the proteasome activity is a major mechanism that causes increased accumulation of ubiquitinated proteins, which are normally degraded by the cellular proteasome machinery (Chung et al, 2005;Kessova and Cederbaum, 2005;Marteijn et al, 2005;Zhang et al, 2005). We therefore tested whether AM114 might inhibit proteasome activity, leading to the accumulation of ubiquitinated proteins in the cells.…”
Section: Resultsmentioning
confidence: 99%
“…These included the 26 S proteasome system, which is responsible for the regulated degradation of many intracellular proteins and is essential for cell survival. Previous work indicates that proteasome function can be inhibited by oxidants and oxidative stress (57,58). Two recent reports indicate that HNE adduction to proteasome subunits inhibits specific catalytic functions and impairs the degradation of protein substrates (59,60).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced activity of CYP2E1 is a common feature of numerous pathologic events induced by ethanol-elicited oxidative stress in liver cells, both in the cytosolic and mitochondrial compartments (12, 13). Loss of proteasome function due to oxidative stress appears to occur from formation of adducts with carbonyls, 4-hydroxynonenal (4-HNE) and 3-nitrotyrosine derived from peroxynitrite (8, 14, 15). The 20S proteasome removes oxidized proteins even after 26S proteasome has been inhibited by oxidants, indicating differential resistance to oxidative insult (10, 16).…”
mentioning
confidence: 99%